2016
DOI: 10.3329/bjvm.v13i2.26627
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Mastitis in Lactating Cows: Comparison of Four Screening Tests and Effect of Animal Factors on Its Occurrence

Abstract: A total of 444 quarter milk samples from 111 crossbred dairy cows were subjected to California mastitis test (CMT), somatic cell count (SCC) test, white side test (WST) and surf field mastitis (SFMT) test to quantify their efficacy in detecting sub clinical mastitis in dairy cows of Bangladesh during the period from 2010 to 2011.Milk samples positive by CMT, SCC, WST and SFMT were 265,230, 225 and 222 respectively. All samples were subjected to cultural isolation (gold standard test for comparison of indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 13 publications
(16 reference statements)
6
25
0
Order By: Relevance
“…Results of the California mastitis test revealed that out of 95 quarter milk samples, the number of samples showing true positive, true negative, false positive and false negative were 44 (86.27%), 32 (72.73%), 7 (13.73%), 12 (27.27%) respectively. These results correspond with the findings of Sharma et al (2010) and Badiuzzaman et al (2015). In our research, the California mastitis test has high percentage sensitivity and specificity (Table 1).…”
Section: Resultssupporting
confidence: 93%
“…Results of the California mastitis test revealed that out of 95 quarter milk samples, the number of samples showing true positive, true negative, false positive and false negative were 44 (86.27%), 32 (72.73%), 7 (13.73%), 12 (27.27%) respectively. These results correspond with the findings of Sharma et al (2010) and Badiuzzaman et al (2015). In our research, the California mastitis test has high percentage sensitivity and specificity (Table 1).…”
Section: Resultssupporting
confidence: 93%
“…Considering physical and chemical changes of milk and isolation of associated organisms, several methods have been developed to identify subclinical mastitis (Badiuzzaman et al, 2015). Among the tests, California Mastitis Test (CMT), White Side Test (WST) and Surf Field Mastitis Test (SFMT) are arguably the reliable screening tests for sub clinical mastitis (Greiner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a study, it was appeared that SCC was the most reliable test and closest to the bacteriological results (Badiuzzaman et al, 2015). So this study used SCC technique to test subclinical mastitis.…”
Section: Detection Of Subclinical Mastitismentioning
confidence: 99%